Prescribing selective serotonin reuptake inhibitors in older age. - Topiwala, A; Chouliaras, L; Ebmeier, K (2014)
Apart from commercial reasons, two motivations have led to the introduction of SSRIs to replace the first and second generation antidepressants already available. One was the search for a more rational treatment, based on specific mechanisms, the other the development of effective treatments with fewer side effects, particularly for older patients, who have a greater sensitivity to cardio-vascular and central nervous system effects. The first has been frustrated up to a point, in that SSRIs and other single mechanism drugs do not appear to be more effective than the earliest relatively non-specific antidepressants. The second has been fulfilled, in that SSRIs generally are better tolerated in older patients and in overdose. However, there is a spectrum of other side effects that are particularly relevant in older age and that need attention when treating depression in this particular patient group.